2023
DOI: 10.3390/molecules28062685
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Constituents of Thesium chinense Turcz and Their In Vitro Antioxidant, Anti-Inflammatory and Cytotoxic Activities

Abstract: Three novel compounds (1–3) along with twenty-six known compounds, two known steroids (4–5) and twenty-four known phenylpropanoids (6–29) were isolated from the whole plant of Thesium chinense Turcz. The structures of the three new compounds were elucidated on the basis of ESI-MS, HR-ESIMS, 1D and 2D NMR, IR, UV spectroscopic data. The absolute stereochemistry of compound 1 was determined by the Gauge-Including Atomic Orbitals (GIAO) method. The in vitro antioxidant, anti-inflammatory and cytotoxic activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Organic acids, for example, caffeic acid and chlorogenic acid, show antioxidant, antibacterial, and anti-inflammatory activities [40,41]. Phenylpropanoids, for example, esculin, shows anti-inflammatory and antioxidative stress effects [42]; pinoresinol-4-O-glucoside shows antioxidant activity [43]; and lariciresinol-4-O-β-D-glucopyranoside shows anti-inflammatory and antiviral effects [44]. It can also be assumed that not only the main chemical constituents with high content but also all of these compounds identified in the Lanqin oral liquid have the probability of being bioactive constituents.…”
Section: Characterization and Identification Of Alkaloidsmentioning
confidence: 99%
“…Organic acids, for example, caffeic acid and chlorogenic acid, show antioxidant, antibacterial, and anti-inflammatory activities [40,41]. Phenylpropanoids, for example, esculin, shows anti-inflammatory and antioxidative stress effects [42]; pinoresinol-4-O-glucoside shows antioxidant activity [43]; and lariciresinol-4-O-β-D-glucopyranoside shows anti-inflammatory and antiviral effects [44]. It can also be assumed that not only the main chemical constituents with high content but also all of these compounds identified in the Lanqin oral liquid have the probability of being bioactive constituents.…”
Section: Characterization and Identification Of Alkaloidsmentioning
confidence: 99%
“…Phytochemical and pharmacological aspects of T. chinense has not been extensively studied. Hitherto, only about 60 compounds including flavonoids, alkaloids, phenylpropanoids, steroids, and fatty acids, have been identified, and flavonoids are recognized as the main chemical constituents of T. chinense [ 9 15 ]. Pharmacological test indicated that T. chinense inhibited mouse auricle swelling caused by xylene, rat foot swelling caused by egg white, rat cotton ball pulp odontoma, and mice’s ear edema caused by xylene [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thesium chinense, a hemiparasitic plant within the genus Thesium of the Santalaceae family, exhibits a widespread distribution across Africa, Europe, Asia and America [6]. Contemporary pharmacological investigations have proved that T. chinense possesses antiinflammation properties [7,8], antimicrobial effect [9][10][11], analgesic activity [12], antioxidant activity [13] and anti-nephropathy [14]. Termed as a "plant antibiotic" [15], T. chinense demonstrates therapeutic potential in addressing various conditions including mastitis, tonsillitis, pharyngitis, pneumonia, and upper respiratory tract infections [9,16,17].…”
Section: Introductionmentioning
confidence: 99%